Criminal Liability of Frotteurism Offenders and Protection For Victims - Fuadi Isnawan (Fakultas Hukum, Universitas Warmadewa, 2024)
Sexual violence is a serious problem in Indonesia with a high rate of cases. Law No. 12 of 2022 on the Crime of Sexual Violence (TPKS) and Law No. 13 of 2006 on Witness and Victim Protection have important urgency in protecting victims of sexual violence, including Frotteurism. Data shows a surge in cases of sexual violence, which includes various forms of harassment in public places, including public transportation. Criminal law protection for victims of Frotteurism is essential to provide fair access to legal services, psychological recovery, and rehabilitation. This research uses normative legal research method with case approach and statutory approach. . The research results of this article Frotteurism is a physical act of sexual harassment that degrades a person's dignity based on their sexuality and/or morality. This act is regulated in Law Number 12 of 2022 on the Crime of Sexual Violence and is subject to a maximum prison sentence of 4 years and/or a fine of IDR 50,000,000. The TPKS Law provides legal protection for victims of sexual violence, including Frotteurism. Victims' rights include the right to handling, protection, and recovery, tailored to the victim's specific situation and needs. Special rights for victims with disabilities are also accommodated. Law No. 13/2006 on Witness and Victim Protection also provides protection for victims of criminal acts, including Frotteurism. The rights of victims are regulated in Article 5 of the Law, including the right to protection of personal security, family, and property, as well as the right to medical assistance, psychosocial rehabilitation, and psychological.